Trade, Technology, and Wages: General Equilibrium Mechanics - Joseph F. Francois; Douglas Nelson (Tinbergen Institute, 1998)
This paper highlights analytical reasons why we believe trade and technology are linked to wagemovements in general, and how we should organize our examination of the recent episode of wage andemployment erosion in the OECD countries. We start with a graphic tour through the mechanics ofgeneral equilibrium theory on trade and wages. This provides a set of implied relationships betweenwages and factor intensity trends that, together, provide a casual test of the consistency of positedrelationships with actual trends. Numeric analysis and a review of the general equilibrium empiricalliterature follow the theoretical overview.
Keywords: 330